EXTH-58. EFFECTS OF TORC1/2 INHIBITOR MLN0128 ALONE AND IN COMBINATION WITH MEK INHIBITION IN BRAF MUTATED GLIOMA MODELS IN VITRO AND IN VIVO - Liu, Kevin X (Neuro Oncol, 2017)
INTRODUCTION: MLN0128, a second-generation ATP-competitive pan-mTOR kinase inhibitor, acts on both mTORC1 and mTORC2. We investigated the effects of MLN0128 monotherapy and in combination with MEK and BRAF(V600E) inhibition in models of pediatric low-grade glioma (PLGG). METHODS: We used human glioma cell lines expressing BRAF(V600E) (AM38), wild-type BRAF (LN229, TN98, SF188) and isogenic systems of KIAA1549:BRAF-expressing NIH3T3 cells. Signaling inhibitors included MLN0128, everolimus, BRAF(V600E) specific inhibitor PLX4720, and MEK specific inhibitors AZD6244 and GSK1120212. Cell proliferation was determined using an ATP-based assay. Biochemical effects were assessed using western blot analysis. The DBTRG (BRAF(V600E)) xenograft mouse model was used to assess in vivo efficacy. RESULTS: MLN0128 monotherapy demonstrates more potent anti-proliferative effects compared to everolimus in all tested PLGG lines independent of BRAF status. As expected, treatment with MLN0128 leads to down-regulation of p-AKT, p-S6 and p-4EBP1, whereas treatment with everolimus only reduces expression of p-S6. MEK inhibition with AZD6244 effectively decreases p-ERK expression in all lines; however, the addition of MLN0128 to AZD6244 causes a rebound in p-ERK expression in BRAF(WT) gliomas but not in gliomas expression BRAF(V600E) or KIAA1549:BRAF alterations. In cells carrying either the BRAF(V600E) or KIAA1549:BRAF alteration, combined treatment with MLN0128 and GSK1120212 or AZD6244 leads to synergistic anti-proliferative effects but such synergy is not evident in BRAF(WT) gliomas. In vivo studies show superior efficacy of combinations of PLX4720 and MLN0128 compared to monotherapies (p<0.02) or combination of PLX4720 + everolimus (p=0.03). CONCLUSION: MLN0128 displays synergistic anti-neoplastic effects with MEK inhibition in gliomas bearing BRAF(V600E) or KIAA1549:BRAF. In BRAF wild-type cells, such synergy is not present, potentially due to rebound in p-ERK when MLN0128 is combined with AZD6244. Combination therapy with MLN0128 + PLX4720 prolongs survival in a BRAF(V600E) mutant glioma model and is superior to monotherapy or everolimus + PLX4720 combination.